2002
DOI: 10.1016/s1535-6108(02)00060-0
|View full text |Cite
|
Sign up to set email alerts
|

Selectively replicating adenoviruses targeting deregulated E2F activity are potent, systemic antitumor agents

Abstract: We have engineered a human adenovirus, ONYX-411, that selectively replicates in human tumor cells, but not normal cells, depending upon the status of their retinoblastoma tumor suppressor protein (pRB) pathway. Early and late viral gene expression as well as DNA replication were significantly reduced in a functional pRB-pathway-dependent manner, resulting in a restricted replication profile similar to that of nonreplicating adenoviruses in normal cells both in vitro and in vivo. In contrast, the viral life cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
153
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(158 citation statements)
references
References 75 publications
5
153
0
Order By: Relevance
“…Recently, using the E2F-1 promoter, which is activated/upregulated in human tumors with defective retinoblastoma (Rb)-mediated cell cycle pathway, several groups have constructed oncolytic adenoviral vectors where the E1A viral gene is placed under the control of E2F-1 promoter. [44][45][46] In vitro and in vivo studies using these vectors showed tumor-cell selectivity and significant antitumor activity in several different human tumor xenografts models.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, using the E2F-1 promoter, which is activated/upregulated in human tumors with defective retinoblastoma (Rb)-mediated cell cycle pathway, several groups have constructed oncolytic adenoviral vectors where the E1A viral gene is placed under the control of E2F-1 promoter. [44][45][46] In vitro and in vivo studies using these vectors showed tumor-cell selectivity and significant antitumor activity in several different human tumor xenografts models.…”
Section: Discussionmentioning
confidence: 99%
“…One such vector is ONYX-015 that contains the E1a gene and uses viral genomic deletion for E1b 55k to interrupt the virus life cycle in the presence of cellular p53 (in normal cells) but not mutant p53 (found in many tumor cells). [7][8][9][10] Although ONYX-015 has shown potential in various laboratory and clinical studies, a lack of correlation between p53 status and viral replication has been reported. 15 Other vectors use tumor-specific promoters for E1 gene expression restricted to tumor cells to facilitate viral replication.…”
Section: Discussionmentioning
confidence: 99%
“…Adenovirus vectors designed for this purpose typically contain the E1A gene and undergo the viral replication cycle selectively in tumor cells that are relatively inactive in p53 and pRb status. Such vectors, that is, ONYX-015 (dl1520) with E1B55-deletion 7 and ONYX-411 containing E1 and E4 genes both under the control of human E2F promoter, 8 have achieved oncolytic effects in various tumors in clinical trials. [8][9][10] Despite this recent progress, adenovirus gene therapy for liver cancer continues to face challenges.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] For example, replication of a recombinant adenoviral vector can be restricted to cells that have a defect in the retinoblastoma (pRB) pathway by replacing the immediateearly E1A promoter in an adenovirus serotype 5 vector (Ad5) with the tumor-specific human E2F-1 promoter. 4,5 Defects in the pRB pathway occur in approximately 80% of all tumors, potentially allowing the use of such oncolytic adenoviral vectors in the treatment of many different types of cancers, possibly without the potential side effects often associated with standard chemotherapy agents. However, to date, oncolytic adenoviral vectors have demonstrated only limited efficacy in the clinic, [6][7][8] prompting the search for methods to increase the potency of these vectors while maintaining their selectivity and safety profile.…”
Section: Introductionmentioning
confidence: 99%